Institutional mapping of government assistance of Local Financial Planning and Management (LFPM) in the Philippines - Javier, Aser B.; Mendoza, Rufo R. (Danyag :the UPV journal of humanities and social sciences, 2007)
"The decentralization and local autonomy integral to the Local Government Code (LGC) of 1991 have endowed considerable regulatory powers to the LGUs and allowed them additional options for revenue generation. However, the same integral elements of the LGC have posed major challenges to the LGUs, especially daunting to the less capable ones. This argument emanates from the general powers and attributes of LGUs as found in Chapter 2, Section 14 of the LGC of 1991 which explicitly described the political and corporate nature of LGUs, "when a new local government unit is created, its corporate existence shall commence upon the election and qualification of its chief executive and a majority of the members of the sanggunian." The challenge, nevertheless, lies in the active participation of institutions both state and non-state, in the form of governance assistance, which by the way is an inherent feature of the LGC. This paper identified and described the various forms of governance assistance provided to LGUs in local financial planning and management (LFPM). The type of assistance was three-fold: financial assistance, technical assistance, and policy assistance. Financial assistance refers to direct financial assistance and credit financing through either loans or grants. Technical assistance refers to the deployment of experts, capacity building, and non-cash support. Policy assistance refers to assistance in developing the regulatory framework and policy directions in LFPM. The study found that the national government, in particular, has provided facilities to enhance the capacity of local governments in planning and managing their financial resources. International organizaitons and funding agencies have provided the three-fold assistance to strengthen the management capacity but also to realize the development goals of the LGUs. Both public and private financial institutions have offered options to finance local development initiatives. The non-government organizations (NGOs) have also re-focused their strategies to enhance participatory local governance among many LGUs through a technical assistance framework anchored in capacity building. Furthermore, academic institutions have continued to support the LGUs through formal and non-formal program offerings and dissemination of knowledge. The study concluded that there is a need to match the assistance provided with the LGU needs and demands. Further, harmonization of key national governmental functions, enhancing the functioning of non-state network in LFPM, strengthening theinternal financial management of LGUs and enhancing alternative revenue generation schemes needs to be looked at for an enhanced LFPM assistance. It also acknowledged that the range of local responses provided that maybe different from known practices are needed beyond current forms assistance."